Qingre Huoxue decoction attenuates myocardial ischemia‒reperfusion injury by regulating the autophagy‒endoplasmic reticulum stress axis via FAM134B-mediated ER-phagy - Li, Rui; Zhang, Jiechun; Ji, Shuliang; Fang, Junfeng; Ji, Xiaodong; Zeng, Yanping; Liu, Nan; Wu, Wei; Liu, Shiyi (Frontiers in Pharmacology, 2024)
Background: Autophagy-endoplasmic reticulum (ER) stress axis dysregulation is linked to myocardial ischemia-reperfusion injury (MIRI), which counteracts the benefits of acute myocardial infarction (AMI) reperfusion therapy. Qingre Huoxue decoction (QRHX) improves the short-and long-term prognosis of AMI after percutaneous coronary intervention and alleviates myocardial injury in AMI rats by stimulating autophagy via the PI3K/Akt pathway. We aimed to further explore the efficacy of QRHX in treating MIRI and its regulatory relationship with FAM134Bmediated ER-phagy.: Rats were administered different concentrations of QRHX for 2 weeks, and then MIRI was induced. Ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS) was used to examine the levels of the main pharmacological metabolites of the serum of rats treated with the drug (QRHX-mediating serum; QRHX-MS). H9c2 cells were pretreated with QRHX-MS for 24 h before being exposed to hypoxia/reoxygenation (H/R). The mechanisms underlying the effects of QRHX-MS were further studied via rescue experiments involving FAM134B knockdown. The myocardial infarct size, cardiac function, morphology and the expression of apoptosis-, autophagy-, and ER stress-related proteins and genes were assessed. The colocalization of autophagosomes with lysosomes and the localization of proteins involved in ER-phagy or autophagic flux in autophagosomes was examined. Results: QRHX decreased the myocardial infarct size and oxidative stress, improved cardiac function and alleviated morphological changes in a dose-dependent manner in MIRI rats by promoting autophagic flux to inhibit ER stress and ER stressrelated apoptosis, which was related to FAM134B-mediated ER-phagy, as revealed by autophagy analysis. UPLC-MS analysis of QRHX-MS revealed 20 major active metabolites of QRHX-MS, including baicalin, cryptotanshinone, 3,4dihydroxybenzaldehyde and caffeic acid. QRHX-MS attenuated H/R-induced cardiomyocyte injury and apoptosis by increasing autophagic flux to suppress ER stress and ER stress-related apoptotic protein and gene expression. When autophagic flux was inhibited or FAM134B was knocked down in H9c2 cells followed by QRHX-MS pretreatment, the protective effect of QRHX was partially reversed. Conclusion: QRHX alleviates myocardial injury, apoptosis and infarct size expansion in MIRI by regulating the autophagy-ER stress axis via FAM134Bmediated ER-phagy.